Estimation of broadband ground motion characteristics considering source parameter uncertainty and undetermined site condition in densely populated areas of Pingwu - Ji, Zhiwei; Li, Zongchao; Sun, Jize; Gao, Mengtan; Li, Tiefei; Huang, Ting; Li, Na; Guo, Xiangyun (Frontiers in Earth Science, 2023)
Three destructive earthquakes occurred in Pingwu and Songpan, Sichuan Province, China, between August 16 and August 23, 1976. Due to the earthquake-monitoring capability at that time, the ground motion characteristics of these earthquakes are very vague. Real and reliable strong ground motion input plays an important role in seismic building design and urban-scale earthquake damage simulation. This study reproduces the main broadband ground motion characteristics of the 1976 Ms7.2 Songpan earthquake in densely populated areas of Pingwu. The empirical Green’s function method and finite difference method are used to simulate high-frequency and low-frequency ground motion, respectively, and the broadband ground motion is obtained by superposition within the frequency range. In addition, in combination with the “Recipe” source parameter scheme, various uncertainties in the source parameters are considered, including the source mechanism, source depth, relevant parameters of asperity, etc. Thirty-six kinds of broadband ground motion are obtained at six typical locations in the Pingwu area. To test the rationality of the obtained broadband ground motion, the broadband ground motion time histories that are consistent with the local ground motion characteristics are selected by using ground motion prediction equations (GMPEs). The results show that the ground motion time history of the earthquake scenario obtained in this paper can meet the destructive capacity of earthquakes of this magnitude and that the hybrid method selected in this paper can effectively compensate for the lack of long-period components of the original empirical Green function method. This research also proves that the peak ground acceleration (PGA) of ground motion is mainly contributed by high-frequency ground motion components and that high-frequency and long-period ground motion contributes strongly to the peak ground velocity (PGV). The basic fortification intensity in the Pingwu area is VIII. In this paper, the corresponding intensity at PWN is VI - VII, indicating that the buildings at this location are less likely to be damaged after the earthquake, while the seismic intensity at other locations is VII - IX, and the buildings at these locations are more likely to be damaged during the earthquake.